Sheltering eaves. 2 - Aruga, Rie (Kodansha USA, 2025)
Both living in a children's home due to abuse, Yoru and Tenjaku only have a year left before they are legally required to leave the home. With stronger feelings developing, Yoru has always felt protected by Tenjaku, but one day, Tenjaku's father reappears without warning. His father wants to reunite and live together as a family...but what will Tenjaku decide to do? Leave behind the years of trauma and forgive, or continue down the path of uncertainty alone?" --